2014
DOI: 10.1161/hypertensionaha.113.01774
|View full text |Cite
|
Sign up to set email alerts
|

Potential Therapeutic Role of Phosphodiesterase Type 5 Inhibition in Hypertension and Chronic Kidney Disease

Abstract: The online-only Data Supplement is available with this article at http://hyper.ahajournals.org/lookup/suppl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 90 publications
1
32
0
1
Order By: Relevance
“…Inhibition of phosphodiesterase 5 increases bioavailability of intracellular cGMP which results in vasodilation and attenuation of hypertension and kidney damage. 45 It was recently reported that upregulation of PDE1C may be involved in cold-induced pulmonary hypertension and pulmonary arterial remodeling. 46 Inhibition of PDE1 eliminated cold-induced macrophage infiltration, NADPH oxidase activation, and superoxide production and reversed pulmonary arterial remodeling.…”
Section: Neurohumoral Dysfunction Plays a Role In Aging-related Vascumentioning
confidence: 99%
“…Inhibition of phosphodiesterase 5 increases bioavailability of intracellular cGMP which results in vasodilation and attenuation of hypertension and kidney damage. 45 It was recently reported that upregulation of PDE1C may be involved in cold-induced pulmonary hypertension and pulmonary arterial remodeling. 46 Inhibition of PDE1 eliminated cold-induced macrophage infiltration, NADPH oxidase activation, and superoxide production and reversed pulmonary arterial remodeling.…”
Section: Neurohumoral Dysfunction Plays a Role In Aging-related Vascumentioning
confidence: 99%
“…In diabetes, glomerular cGMP production is decreased, PDE5 activity is increased11 and changes in the cGMP-NO pathway leads to a rise in intra-glomerular pressure12. PDE5 inhibitors (PDE5is) may have an active role in the management of DN13 by reducing glomerulosclerosis and proteinuria and improving vascular inflammation and podocyte count in experimental diabetes models14151617. These findings, together with the modulation of inflammatory1418 and angiogenic mediators, and endothelial function1920 in murine and human models, support the use of PDE5i to prevent complications of the diabetic kidney.…”
mentioning
confidence: 99%
“…MBF to the renal medulla can be importantly controlled by the constriction and dilation of the descending vasa recta (VR) capillaries, which branch from the efferent arterioles of the juxtamedullary glomeruli (49,147,149) and whose tone is controlled by the smooth muscle-like pericytes (49, 90, 146 -149). The role of NO cross talk from mTAL to surrounding VR in the renal medulla has been reviewed in detail elsewhere (19,33) and will be discussed here largely with regard to its ROS-related counterregulatory functions. The present review will first summarize data showing that either the excess endogenous production or reduced scavenging of O 2 ·Ϫ or H 2 O 2 within the renal medulla results in a decrease in MBF and Na ϩ excretion, leading to hypertension and renal injury.…”
mentioning
confidence: 99%